Reviving the American dream : the economy, the states & the federal government - Rivlin, Alice M. (Washington, D.C. : Brookings Institution, 1992)
The American dream is fading: for nearly two decades, the economy has been performing below par, the quality of life has deteriorated, and the government has not confronted the public problems that concern citizens most. In this provocative book, Alice Rivlin offers a straightforward, nontechnical look at the issues threatening the American dream and proposes a solution: restructure responsibilities between the federal and state government. Under her plan, the federal government would eliminate most of its programs in education, housing, highways, social services, economic development, and job.
The Economic Challenge -- The Institutional Challenge -- Improving the Policy Process -- Recommended Readings -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W -- Y
Includes bibliographical references (pages 183-187) and index.
Print version record.
English.
JSTOR
Keywords: Intergovernmental fiscal relations -- United States; Federal government -- United States; United States -- Economic policy -- 1981-1993.; Industrial productivity -- United States; Productivité -- États-Unis.; Relations fiscales intergouvernementales -- États-Unis.; Gouvernement fédéral -- États-Unis.; États-Unis -- Politique économique -- 1981-1993.; BUSINESS & ECONOMICS -- Public Finance; Economic policy; Federal government; Industrial productivity; Intergovernmental fiscal relations; United States; Föderalismus; Wirtschaftspolitik; Produktivität; USA; Economische politiek; POLITICAL SCIENCE / American Government / State; 1981-1993